Representasi Perempuan dalam Perselingkuhan : Critical Language pada Judul Rubrik ”Ambyar” Radarsemarang.id - Sigit Andrianto; Sheila Lestari Giza Pudrianisa (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2023)
The Radarsemarang.id media portal has a section entitled “Ambyar”, which contains stories of domestic conflicts that ended in divorce. This rubric is delivered using popular language style and tends to be humorous. However, the writings in this rubric present men and women unequally. As a mass media, Radarsemarang.id has the power to shape reality. This paper dismantles how women are described in infidelity using a qualitative approach using Roger Fowler's Critical Linguistic discourse analysis model. Stuart Hall's representational theory is used as a basis for analysis. This analysis resulted in a selection of vocabulary in the form of a strategy of limiting views, women are always described as perpetrators and men are described as victims in an affair. Through grammar, namely the